1998
DOI: 10.1002/(sici)1096-9861(19980817)398:1<1::aid-cne1>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptidergic control of the optic gland ofOctopus vulgaris: FMRF-amide and GnRH immunoreactivity

Abstract: In cephalopods, the endocrine optic glands on the optic tract control the maturation of the gonads. The glands are innervated by the optic gland nerve, which originates in the central nervous system. To explore the involvement of neuropeptides in the nervous control of the optic gland of Octopus vulgaris, the presence and distribution of Phe-Met-Arg-Phe-NH2 (FMRF-amide)-like and gonadotropin releasing homone (GnRH)-like peptides were examined in the central nervous system and optic gland by immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 47 publications
10
74
1
Order By: Relevance
“…Our findings extend current knowledge on the optic gland as an endocrine organ involved in the sexual maturation and reproduction (Young, 1971;Di Cosmo and Di Cristo, 1998). Varicose cChAT-positive fibers and terminals were often situated close to endocrine cells, mimicking the axosomatic synapses.…”
Section: Immunohistochemistrysupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings extend current knowledge on the optic gland as an endocrine organ involved in the sexual maturation and reproduction (Young, 1971;Di Cosmo and Di Cristo, 1998). Varicose cChAT-positive fibers and terminals were often situated close to endocrine cells, mimicking the axosomatic synapses.…”
Section: Immunohistochemistrysupporting
confidence: 87%
“…Some of these peptides are proposed to exist in the octopus. These include somatostatin (Feldman, 1986), FMRF-amide (Di Cosmo and Di Cristo, 1998;, gonadotropin-releasing hormone (Di Cosmo and Di Cristo, 1998;Iwakoshi-Ukena et al, 2004), galanin (Suzuki et al, 2000), neuropeptide Y (Suzuki et al, , 2003, calcitonin gene-related peptide , and corticotropin-releasing factor (Suzuki et al, 2003). These peptides have been localized in octopus by immunohistochemistry, mostly using antibodies against vertebrate-type peptides.…”
Section: Neurotransmitter-linked Molecules In Cephalopods and Vertebrmentioning
confidence: 99%
“…Its presence was once thought to be restricted to members of Phylum Chordata, but increasing evidence suggests otherwise. A large number of studies reported the presence of GnRH-immunoreactivity (ir) and bioactivity in the gastropods (Goldberg et al, 1993;Young et al, 1999;Zhang et al, 2000;Tsai et al, 2003), bivalves (Pazos and Mathieu, 1999;Nakamura et al, 2007), polyplacophorans , cephalopods (Di Cosmo and Di Cristo, 1998;Di Cristo et al, 2002), cnidarians (Anctil, 2000;Twan et al, 2006), and platyhelminthes (Anctil and Tekaya., 2005). Importantly, a dodecapeptide containing the structural core of chordate GnRH was isolated from the central nervous system (CNS) of the common octopus (Iwokoshi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Very uncommonly for cephalopods, O. vulgaris has an internal fertilization that takes place in the oviducal gland. The secretory activity of the oviducal gland is under the control of neuropeptides and sex steroid hormones (Di Cosmo and Di Cristo, 1998;Di Cosmo et al, 2001;Di Cristo et al, 2002;Di Cristo et al, 2005;Di Cristo et al, 2008). An octopus male introduces a large amount of spermatozoa in the female oviducts through a hectocotylized arm; these cells are enveloped in spermatophores.…”
Section: Discussionmentioning
confidence: 99%